2017
DOI: 10.1039/c6sc03635j
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogenic protein labeling using a genetically encoded unstrained alkene

Abstract: A new fluorogenic bioorthogonal reaction between styrene (an unstrained alkene) and a tetrazine was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…In our previously report, an inverse electron-demand Diels-Alder (iEDDA) reaction between KStyr and tetrazine was examined for fluorogenic protein labeling. 10 It was intriguing that styrene could serve as a versatile reagent for two different fluorophore-forming bioorthogonal reactions. By employing our previously identified pyrrolysyl-tRNA synthetase (PylRS) mutant-tRNA Pyl pair, 10 we were able to obtained 25 mg/L of sfGFP mutant (sfGFP-Asn149KStyr) that contains KStyr at position Asn149.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previously report, an inverse electron-demand Diels-Alder (iEDDA) reaction between KStyr and tetrazine was examined for fluorogenic protein labeling. 10 It was intriguing that styrene could serve as a versatile reagent for two different fluorophore-forming bioorthogonal reactions. By employing our previously identified pyrrolysyl-tRNA synthetase (PylRS) mutant-tRNA Pyl pair, 10 we were able to obtained 25 mg/L of sfGFP mutant (sfGFP-Asn149KStyr) that contains KStyr at position Asn149.…”
Section: Resultsmentioning
confidence: 99%
“…10 It was intriguing that styrene could serve as a versatile reagent for two different fluorophore-forming bioorthogonal reactions. By employing our previously identified pyrrolysyl-tRNA synthetase (PylRS) mutant-tRNA Pyl pair, 10 we were able to obtained 25 mg/L of sfGFP mutant (sfGFP-Asn149KStyr) that contains KStyr at position Asn149. In a typical labeling experiment, sfGFP-Asn149KStyr was incubated with 500 μM tetrazole in PBS buffer under UV irradiation at 302 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Protein expression was carried out in LB medium supplemented with and without 1 mM CbK. Fluorescence analysis of E. coli cultures showed that full-length sfGFP protein was produced only in the presence of CbK (Fig.…”
mentioning
confidence: 99%
“…With the purified sfGFP-N149CbK in hand, we explored the inverse Diels-Alder reaction between the recombinant sfGFP-N149CbK and a commonly used tetrazine scaffold 4041 containing a fluorescein conjugate (Fl-Tet; Fig. 1).…”
mentioning
confidence: 99%